Early detection of language categories in face perception - Cristina Baus (Nature Portfolio, 2021)
Abstract Does language categorization influence face identification? The present study addressed this question by means of two experiments. First, to establish language categorization of faces, the memory confusion paradigm was used to create two language categories of faces, Spanish and English. Subsequently, participants underwent an oddball paradigm, in which faces that had been previously paired with one of the two languages (Spanish or English), were presented. We measured EEG perceptual differences (vMMN) between standard and two types of deviant faces: within-language category (faces sharing language with standards) or between-language category (faces paired with the other language). Participants were more likely to confuse faces within the language category than between categories, an index that faces were categorized by language. At the neural level, early vMMN were obtained for between-language category faces, but not for within-language category faces. At a later stage, however, larger vMMNs were obtained for those faces from the same language category. Our results showed that language is a relevant social cue that individuals used to categorize others and this categorization subsequently affects face perception.